Ceftolozane-tazobactam compared with levofloxacin in the treatment of complicated urinary-tract infections, including pyelonephritis: a randomised, double-blind, phase 3 trial (ASPECT-cUTI). Issue 9981 (16th May 2015) - Wagenlehner, Florian M; Umeh, Obiamiwe; Steenbergen, Judith; Yuan, Guojun; Darouiche, Rabih O
Summary: Background: Treatment of complicated urinary-tract infections is challenging due to rising antimicrobial resistance. We assessed the efficacy and safety of ceftolozane-tazobactam, a novel antibacterial with Gram-negative activity, in the treatment of patients with complicated lower-urinary-tract infections or pyelonephritis. Methods: ASPECT-cUTI was a randomised, double-blind, double-dummy, non-inferiority trial done in 209 centres in 25 countries. Between July, 2011, and September, 2013, hospital inpatients aged 18 years or older who had pyuria and a diagnosis of a complicated lower-urinary-tract infection or pyelonephritis were randomly assigned in a 1:1 ratio to receive intravenous 1·5 g ceftolozane-tazobactam every 8 h or intravenous high-dose (750 mg) levofloxacin once daily for 7 days. The randomisation schedule was computer generated in blocks of four and stratified by study site. The next allocation was obtained by the study site pharmacist via an interactive voice-response system. The primary endpoint was a composite of microbiological eradication and clinical cure 5–9 days after treatment in the microbiological modified intention-to-treat (MITT) population, with a non-inferiority margin of 10%. This study is registered withClinicalTrials.gov, numbersNCT01345929 andNCT01345955 . Findings: Of 1083 patients enrolled, 800 (73·9%), of whom 656 (82·0%) had pyelonephritis, were included in the microbiological MITT population. Ceftolozane-tazobactam was non-inferior to levofloxacin for composite cure (306 [76·9%] of 398 vs 275 [68·4%] of 402, 95% CI 2·3–14·6) and, as the lower bound of the two-sided 95% CI around the treatment difference was positive and greater than zero, superiority was indicated. Adverse event profiles were similar in the two treatment groups and were mainly non-serious. Interpretation: Treatment with ceftolozane-tazobactam led to better responses than high-dose levofloxacin in patients with complicated lower-urinary-tract infections or pyelonephritis. Funding: Cubist Pharmaceuticals.